Organizational fit : key issues and new directions - Kristof-Brown, Amy L.; Billsberry, Jon (Wiley-Blackwell, 2013)
"An ambitious survey of the field, by an international group of scholars, that looks toward the future of person-organization fit. Explores how people form their impressions of fit and the impact these have on their behavior, and how companies can maximize fit Includes multiple perspectives on the topic of how people fit into organizations, discussing issues across the field and incorporating insights from related disciplines Actively encourages scholars to take part in organizational fit research, drawing on workshops and symposia held specially for this book to explore some of the creative directions that the field is taking into the future "--